A qualitative exploration among the staff of an antiretroviral therapy center in (central) India regarding factors associated with job satisfaction, patient satisfaction and treatment success - Joshi, Sudhir Chandra; Bamboria, B. L.; Joshi, Rita (International Journal of Advances in Medicine, 2018)
Background: Perception of the staff of an Anti Retroviral Therapy Center (ARTC) was explored regarding the organizational culture of the center with special reference to its effectiveness and efficiency. Methods: This qualitative exploration was conducted in the ARTC, RDGMC Ujjain. Data were collected during April 2016 and March 2018 by means of 35 self-administered-open-ended questionnaires as well as interviews (3 Focus Group Discussions and 5 Face to Face In-Depth Interviews). Data consisting of the text of the questionnaire responses and transcripts of the interview-sound files were subjected to thematic (content) analysis method. Results: Several praiseworthy features as well as deficiencies were identified, most important among them were related to counseling, behavior and management of investigations as well as treatment. Emphasis was on finding out effective and efficient ways to prevent LTFUs/ defaults/ delays. In the process of analysis of the data, three themes emerged. These are: theme 1 “general domains for attention and emphasis”; theme 2 “specific areas identified for further improvement” and theme 3 “suggestions for improvement and conclusions of the analysis of the situation”. Several measures were suggested in the interest of the PLHIV and the institution as well as for achievement of the global and national targets. Conclusions: For improvement in treatment coverage and success, escalation of certain inputs within a timeframe is essential while aiming at certain outputs is also urgently needed simultaneously. Among these, improving the staffing of the ART center in quality and quantity, the job satisfaction of the staff and patient satisfaction are extremely important.